Tislelizumab (anti-PD-1) plus chemotherapy as neoadjuvant therapy for patients with stage IB3/IIA2 cervical cancer (NATIC): a prospective, single-arm, phase II study - Jindong Sheng; Haitao Luo; Xiangyu Liu; Chunyan Liu; Wenhao Zhou; Yujie Zhao; Ruoyan Liu; Dan Li; Changxiao Xu; Bo Yang; Ying Liu; Xin Fu; et al. (Signal Transduction and Targeted Therapy)
Abstract The clinical benefit of neoadjuvant immunochemotherapy in locally advanced cervical cancer (LACC) remains unclear. This single-arm, phase II study (Chinese Clinical Trial Registry, ChiCTR2200065392) aimed to evaluate the efficacy and safety of neoadjuvant anti-programmed cell death protein 1 (PD-1) antibody tislelizumab in combination with chemotherapy in treatment-naïve patients with stage IB3/IIA2 LACC. Enrolled patients received tislelizumab (200 mg, every 3 weeks) plus chemotherapy for 3 cycles before radical surgery. The primary endpoint was the pathological complete response (pCR). Secondary endpoints were objective response rate (ORR) per Response Evaluation Criteria in Solid Tumors version 1.1, disease-free survival, overall survival, and safety. Exploratory endpoints included tissue-based and blood-based biomarkers to identify the biological drivers behind the clinical outcomes. Between November 2022 and March 2024, 30 patients were enrolled. All patients completed 3 cycles of neoadjuvant immunochemotherapy and underwent radical surgery. The pCR was observed in 20 (66.7%) patients, and 4 (13.3%) patients achieved major pathological response (MPR), with an optimal pathological response rate (OPR) of 80.0%. The ORR was 90.0%, with 17 (56.7%) complete responses. Survival data were immature at the median follow-up of 14.7 months (data cutoff, December 31, 2024). Grade 3 treatment-related adverse events (TRAEs) and immune-related AEs occurred in 26.7% and 3.3% of patients, respectively. No treatment-related death occurred. Patients with pCR had significantly higher expression of PD-L1 CPS at baseline, and a strong relationship with immune-related signature (all p < 0.05). Neoadjuvant tislelizumab plus chemotherapy showed promising antitumor efficacy and a well-tolerated safety profile in patients with stage IB3/IIA2 LACC, and might be a potential option in this population.